2000
DOI: 10.1039/a906181i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis conditions for hexagonal mesoporous silica layers

Abstract: Hexagonal mesoporous silica layers were prepared by the sol±gel route using silicon alkoxides as silica precursors and alkyltrimethylammonium bromides to form the templating liquid crystal mesophase. The synthesis conditions required to obtain well-ordered crack-free layers were investigated. Thin layers exhibiting these properties were deposited from diluted sols. X-Ray diffraction enabled characterisation of the thermal evolution of their ordered structure and crystalline texture. Their porosity was experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
107
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 31 publications
8
107
0
Order By: Relevance
“…3(b)) is designated as a Type IVc (mesopores) in the IUPAC classification (Sing et al, 1985), the four others are composite isotherms of Type I (micropores) and Type IVc (mesopores). Similar composite isotherms have been already obtained on ordered hexagonal silica powders (Albouy and Ayral, 2002) and layers (Klotz et al, 2000) in the case of nitrogen adsorption at 77.4 K.…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…3(b)) is designated as a Type IVc (mesopores) in the IUPAC classification (Sing et al, 1985), the four others are composite isotherms of Type I (micropores) and Type IVc (mesopores). Similar composite isotherms have been already obtained on ordered hexagonal silica powders (Albouy and Ayral, 2002) and layers (Klotz et al, 2000) in the case of nitrogen adsorption at 77.4 K.…”
Section: Resultssupporting
confidence: 70%
“…Usually composite isotherms are obtained with N 2 as adsorptive on micro/mesoporous silica materials, from which the microporosity can be evaluated with different methods (Albouy and Ayral, 2002;Klotz et al, 2000;Colomer and Anderson, 2001;Poladi and Landry, 2002). In the case of microporous materials as those used in gas separation and methane storage, Lozano-Castello et al (2002) have suggested that the most important parameter is the micropore size distribution They have estimated it in microporous carbon materials from high-pressure CO 2 and CH 4 adsorption isotherms around ambient temperature by application of the General Adsorption Isotherm model (McEnaney et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…The ordered structure of MCM-41 and SBA-15 is a honeycomb type hexagonal array of regular non-crossing pores-channels with a narrow pore size distribution. The walls of the channels have a definite thickness and are constituted of amorphous SiO 2 [1,2]. The channel diameter can be tuned from 3 to 50 nm depending on the synthesis conditions [3].…”
Section: Introductionmentioning
confidence: 99%
“…These membranes have been tested in selective Na þ /K þ transport. Periodic mesoporous materials have attracted considerable attention during the last decade because of their promising applications as membranes or as hosts for functional membrane materials [55,56]. Many of these applications benefit from arrangements of preferentially aligned, ordered arrays of certain mesostructures.…”
Section: Dynamic Site Complexant Membranesmentioning
confidence: 99%